Gender representations of female perpetrators of intimate partner violence. Issue 3 (12th October 2017) - Walker, Jenna; Ashby, Jo; Gredecki, Neil; Tarpey, Emma
Abstract : Purpose: The purpose of this paper is to understand the constructions of female-perpetrated intimate partner violence (IPV) among postgraduate (PG) students studying and preparing for a career in forensic psychology. A social constructionist methodological framework was adopted in order to explore students' dominant discourses surrounding gender and IPV. Of particular interest was how female perpetrators of IPV within heterosexual relationships were constructed and subsequently positioned by students in terms of social and gender identity. Implications regarding future practice for graduates in relation to risk assessment and treatment interventions are discussed. Design/methodology/approach: Six female PG forensic students took part in a qualitative focus group and discussed their understanding of IPV and views regarding perpetration. Focus group members were also asked to discuss details of a vignette depicting a violent relationship where gender identity was purposefully removed. The focus group interview data were analysed using Foucauldian discourse analysis. Findings: The students constructed IPV as a behaviour that was predominantly perpetrated by men towards women. Students acknowledged that female-perpetrated IPV occurred; however, such behaviour was constructed as non-threatening, and subsequently, less serious than male-perpetrated IPV. Moreover, the analysis revealed that the overall discourses drawn on by the students projected a feminine representation of female IPV that positioned women as emotionally unstable, vulnerable and acting in self-defence. Research limitations/implications: Students' constructions of female-perpetrated IPV appeared to minimise aggression. It is argued that the positioning of women in terms of vulnerability serves to undermine any responsibility for perpetrating violence among this group of students. In terms of implications for practice, oversimplified assumptions in relation to gendered constructions have the potential to inhibit female IPV from being recognised as a serious form of aggression, and it is argued that this could potentially bias assessments of risk leading to an under-estimation of threat. Female perpetrators of IPV may subsequently receive inadequate supervision and intervention and inadequate levels of victim safety planning may occur. These gendered constructions may also inhibit male victims from seeking help and help being offered. Originality/value: This paper highlights the importance of understanding constructions of IPV among students who are preparing for careers as a forensic psychology practitioner. Female IPV is clearly challenging. With respect to the social construction of IPV, the students in this study made many assumptions about female identity by linking this to feminine and essentialist ideas that constrain women as emotionally and biologically vulnerable. Such findings raise questions about whether future training and study programmes are equipped to critically challenge the dominant discourses and subsequent constructions of gender and IPV. Thus, this study has highlighted the need for further research around constructions of IPV in this field of work in order to fully examine potential knowledge gaps in training and teaching of future forensic practitioners.